A reconsideration of the Ora Benin relationship (2014)
The relationship between the Edo people of Ora and the Edo people of Benin dates back to ancient times. It is taken for granted in the accounts of the origin of this relationship that the Ora are the descendants of Uguan, son of Oba Ozolua of the Benin Kingdom. However, a painstaking dissection of certain aspects of the traditions oforigin provides grounds for exploring some of the issues that may have been forgotten or become unremembered in the historical accounts. Whereas the Edo people of Benin place the beginning of their relationship with the Ora in the aftermath of the rule of Ewuare the Great in the 15th century, Ora remembrance of its Benin affiliation goes back as far as the reign of Eweka I in the 13th century. While it is not to be doubted that waves of migration from Benin led to the peopling of the Ora area, it also stands to reason that the Benin migration met an autochthonous element from which has been handed down some of the distinctive and longstanding features of Ora culture still in evidence today. These features include, but are not limited to, the Ora gerontocratic system of traditional governance and the absence of royal art in the Ora area, which mark major departures from the Benin way. In addition, there are extant contributions to Ora culture from the nearby culture of lle-Ife, and these contributions appear to predate the Benin migration, even though the latter dominates accounts of the origin of the Ora.